An Empirical Study On Qris Implementation For Enhancing Sustainability Of MSMEs In Medan City - Rahmayati, Rahmayati; Kurnia, Efry (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2023)
This study aims to determine the factors that influence the use of QRIS for MSMEs in Medan City. QRIS is a practical and efficient development of cashless payment instrument technology. This study uses quantitative methods by collecting observation data and questionnaires from MSME actors in the city of Medan, totaling 171 business actors who use QRIS with sample collection through the purposive sampling method. This study used SPSS program statistics. The results revealed that there is an influence on the benefits and ease of being interested in using QRIS where in transactions buyers do not need to use non-cash money and merchants do not need to provide change. However, there are still few business activities that use cashless payments and some merchants also lack education or are not familiar with QRIS enough because there is still a lack of socialization for MSME players regarding the use of QRIS and some MSME business actors in.